Assessment of the sustainable offshore wind potential in Portugal - Costa, P. (2013)
The sustainable offshore wind potential for the west and south coasts of Portugal is presented. Results were carried out using an atmospheric mesoscale model and GIS tools. Unlike previous common opinions, the preliminary results show the existence of interesting areas for the developing of offshore wind parks.